Modelling and Simulation of Fermentation Product Purification for Local Vinegar using Batch Distillation - Bt Bakar, Faezah (Universitas Ahmad Dahlan, 2014)
Batch distillation has important due to its flexibility and capability to produce high purity product. The simulation of batch distillation columns during steady state operations is a very challenging modelling problem because of the complex dynamic behaviour. In order to verify this issue, simulation of this batch distillation column is to be performed by using computer aided design software and mathematical model .This study is required to model and simulate of fermentation product purification using batch distillation. This research was done by using graphical method and simulating by using MATLAB software that simple model had been presented. The results from these simulations were used as a basis to validate the results obtained (by others) experimentally. As conclusion, distillate and bottoms composition for ethanol drop gradually over time by using graphical method and the trend from simulation showed that the distillate and bottoms composition for ethanol increase and decrease over the time respectively. The declining trend was due to the unsteady state nature of batch distillation, where the lighter component at the bottoms will deplete over time.